THE IMPACT OF THREE COGNITIVE TRAINING INTERVENTIONS ON OLDER ADULTS’ LIFESPACE ACROSS FIVE YEARS - Ross, L. (Innov Aging, 2017)
Lifespace is the purposeful movement throughout one’s environment and is a central aspect of healthy aging. As fluid cognitive abilities are strongly linked to lifespace, targeted cognitive interventions may preserve lifepace in older adults. The objective of this study was to assess the effects of three separate cognitive interventions (reasoning training, speed of processing training, and memory training) on changes in older adults’ lifespace across 5 years. Participants (age range 65–94, M=73.64) randomized to a no-contact control condition (n=698) were compared to those randomized to: reasoning (n=694), speed of processing (n=702), and memory (n=703) training using multilevel modeling. Intention-to-treat (ITT, randomization to training conditions) and dosage (treatment-received via number of training sessions) analyses were conducted. Models were adjusted for age, race, attrition, gender, mental status, driving status, study location, and residential status (i.e. living alone or not). Results revealed no significant group differences in the ITT analyses. However, dosage models revealed that more sessions of speed of processing [95% CI: .0002, .0098] and reasoning [95% CI: .0002, .0100] training predicted greater lifespace across the five years relative to the control group. Participants randomized to memory training did not differ from the control group in lifespace across five years [95% CI: -.0044, .0055]. This is the first study to show that two cognitive interventions (reasoning and speed of processing training), but not memory training, transferred to maintained lifespace across five years. Future research should investigate the mechanisms of these far transfer effects.